The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ani11051256
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Protein Disappearance of Raw Chicken as Dog Foods Decreased by Thermal Processing, but Was Unaffected by Non-Thermal Processing

Abstract: The objectives of the present study were to determine the influence of thermal and non-thermal processing procedures on in vitro ileal disappearance (IVID) of dry matter (DM) and crude protein (CP) in chicken meat as dog foods using 2-step in vitro assays. In thermal processing experiments, IVID of DM and CP in chicken meat thermally processed at 70, 90, and 121 °C, respectively, with increasing processing time was determined. For non-thermal processing experiments, IVID of DM and CP in chicken meat processed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…2). Other applications include evaluation of protein (Kim et al, 2021) or lipid digestibility and bioaccessibility of micronutrients such as vitamins, minerals (van Zelst et al, 2015;Lee et al, 2017) or phytoconstituents like polyphenols. In addition to digestibility, in vitro models can provide valuable information on fibre effects on gut microbiota composition and activity, through SCFA/BCFA, ammonia or gas measurements (Bosch et al, 2008;Cutrignelli et al, 2009;Van den Abbeele et al, 2020a).…”
Section: Potential Applications Of Canine Gut Models In Food and Pharmamentioning
confidence: 99%
See 1 more Smart Citation
“…2). Other applications include evaluation of protein (Kim et al, 2021) or lipid digestibility and bioaccessibility of micronutrients such as vitamins, minerals (van Zelst et al, 2015;Lee et al, 2017) or phytoconstituents like polyphenols. In addition to digestibility, in vitro models can provide valuable information on fibre effects on gut microbiota composition and activity, through SCFA/BCFA, ammonia or gas measurements (Bosch et al, 2008;Cutrignelli et al, 2009;Van den Abbeele et al, 2020a).…”
Section: Potential Applications Of Canine Gut Models In Food and Pharmamentioning
confidence: 99%
“…BCFA, branched-chain fatty acids; GIT, gastro-intestinal tract; SCFA, short-chain fatty acids Effect of supplementation with Black Soldier fly (Hermetia illucens) larvae meal in extruded dog food on in vivo and in vitro digestibilityKim et al, 2021 …”
mentioning
confidence: 99%
“…It is well-known that high temperatures during the processing systems adversely affect the digestibility of protein in animal by-product meal [ 28 , 29 ]. As reported by FEDIAF (the European Pet Food Industry Federation) [ 30 ], the normal digestibility range should be approximately 80%; an investigation of our results in dogs fed either coarse, fine, or very fine diets showed a digestibility of protein within the range of 92.8–95.1%.…”
Section: Discussionmentioning
confidence: 99%
“…The applicant provided many publications at this respect. Some of these publications review the use of in vitro methods and their usefulness to study the digestion in dogs (Harmon, 2007 ; De Godoy et al, 2016 ; Deschamps et al., 2022 ); others provide data on in vitro studies only (Van Zelst et al, 2015 ; Lee et al, 2017 ; Kim et al., 2021 ) or do not allow for a full comparison of the results with those obtained in vivo (Gajda et al., 2005 ); a couple describe methods that may not be comparable to the one described by Boisen in 2007 (Smeets‐Peeters et al, 1999 ; Bosch et al, 2016 ); and some were developed from Boisen's or can be considered comparable but do not provide validation of in vivo reference values at pre‐caecal level (Dufour‐Etienne et al, 1992 ; Tonglet et al, 2001 ; Hervera et al, 2007 ; Hervera et al, 2009 ; Hooda et al, 2012 ; Biagi et al, 2016 ; Penazzi et al, 2021 ). Some of the latter showed good correlation between the digestibility coefficients in vitro and in vivo (faecal data); the conditions of the studies and diets evaluated may play a major role in the correlations observed.…”
Section: Assessmentmentioning
confidence: 99%